If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(-8 + r) = -99 (-8 * -9 + r * -9) = -99 (72 + -9r) = -99 Solving 72 + -9r = -99 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-72' to each side of the equation. 72 + -72 + -9r = -99 + -72 Combine like terms: 72 + -72 = 0 0 + -9r = -99 + -72 -9r = -99 + -72 Combine like terms: -99 + -72 = -171 -9r = -171 Divide each side by '-9'. r = 19 Simplifying r = 19
| 80j^2-95+15=0 | | (6x-20)=(2x+36) | | 16-ln(5-x)=0 | | x(x-20)+3(x-20)=0 | | 20+4n=-6(3n-7) | | 9r^2-39r+44=4 | | 20=(2x-a)(a+2) | | 2w-13w=66 | | 3x+16-3x=16 | | 1n-7=22.5 | | -5m-9=1 | | 7p^2+84=-49p | | 5(x+3)=-10(x+2) | | -86+2x=-4x+118 | | 5x-3x=36 | | 6d-4d=16-9d | | 3.5x+2x+y+y=120.19 | | 3(8-3)=5(2+t) | | 9x^2=4-7x | | Z^2=3+41 | | 32k^2-50=0 | | 2v^2-v-21=0 | | 9-6x=8x^2 | | 1+9x= | | 3v+4x=5 | | 2-2ax+5x-12=0 | | 3(-9)+(2)(-6)= | | 11x+12=23 | | ((-7)-3)((-3)-(-10))= | | -33=9b-8b | | -6-6(-6z+3)=-2(z-3)+4 | | -6n+-1+7=-5 |